Disrupted mucosal vascular barrier in eosinophilic esophagitis - Marco Vincenzo Lenti; Carlo Maria Rossi; Renato Cannizzaro; Giovanni Santacroce; Michela Lizier; Giulia Fornasa; Stefania Merli; Alessandra Pasini; Edoardo Vincenzo Savarino; Paola Spessotto; Michele Di Stefano; Aurelio Mauro; et al. (Scientific Reports)
Abstract Esophageal barrier has been investigated until now on the epithelial side only. Gut vascular barrier dysfunction has been recently implicated in a number of immune-mediated gastrointestinal disorders. We here characterized the esophageal vascular barrier (EVB) in eosinophilic esophagitis (EoE). Probe-based confocal laser endomicroscopy (pCLE) was performed in two EoE and two reflux esophagitis (RE) patients. The vascular barrier marker plasmalemma vesicle-1 (PV-1) was investigated as a measure of barrier disruption, by both immunohistochemistry and qPCR, in esophageal biopsies of 16 patients with EoE, 15 with RE, and 15 healthy controls (HC). In EoE, but not RE, pCLE revealed leakage of the EVB, which was restored in one patient after dupilumab treatment. PV-1 was significantly increased in EoE in comparison to RE and HC, both in terms of protein and transcript levels, supporting vascular leakage. EVB is disrupted in active EoE. Further studies are needed to understand the diagnostic and pathogenic implications of this finding.